Prevalence of undetectable and suppressed viral load in HIV-infected pregnant women initiating Option B+ in Uganda: an observational study nested within a randomized controlled trial - Grace Gabagaya; Gordon Rukundo; Alexander Amone; Priscilla Wavamunno; Joyce Namale-Matovu; Irene Lubega; Clemensia Nakabiito; Zikulah Namukwaya; Monica Nolan; Samuel S. Malamba; Rachel King; Jaco Homsy; et al. (BMC Infectious Diseases, 2021)
Abstract Background Viral load (VL) testing is key in monitoring adherence to antiretroviral therapy (ART) and documenting HIV treatment response. As per HIV treatment guidelines in Uganda, the first VL test is recommended 6 months after initiation of ART. Undetectable VL (uVL) at ART initiation may be helpful in detecting elite controllers in the absence of previous ART use. We investigated viral suppression at ART initiation among a cohort of HIV-positive pregnant women enrolled in the Friends for Life Circles (FLC) for Option B+ randomized controlled trial (RCT). Methods Pregnant women ≥ 18 years of age testing positive for HIV at their first antenatal care visit and starting on ART Option B+ as per the National PMTCT Program guidelines were enrolled into the FLC for Option B+ RCT in urban Kampala and rural Mityana districts of Uganda. Each participant had whole blood samples collected at enrolment to assess baseline VL. Plasma HIV-1 RNA was quantified using COBAS Ampliprep /COBAS Taqman. Baseline VL below 400 RNA copies/ml was considered as viral suppression while baseline VL below 20 RNA copies/ml was considered uVL. Results The mean duration from the date of ART initiation to time of sample collection for baseline VL assessment was 4.4 days (SD 3.6). Of the 532 HIV-positive pregnant women enrolled in the FLC for Option B+ study and newly starting Option B+ without a self-reported history of prior ART use, 29 (5.5%) had uVL and 113 (21.4%) had suppressed VL at baseline. There was no association between participants’ age, gravidity, marital status, mean monthly income, educational level, disclosure of HIV status to partner, and uVL or viral suppression at baseline. However, non-disclosure of HIV status to any other person was associated with decreased odds of viral suppression at baseline (OR 0.640; 0.416–0.982). Conclusion Twenty-one percent of HIV-positive Ugandan pregnant women initiating ART (Option B+) showed virological suppression at baseline and were presumed to be “elite controllers” or to have misreported being ART-naive. Further studies are needed to better understand the biologic mechanisms of elite controllers among pregnant women as well as to differentiate elite controllers from concealed ART use. Trial Registration The trial was registered as NCT02515370 (04/08/2015) on Clinicaltrials.gov.